2015
DOI: 10.1016/j.sleh.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Young Adolescent Sleep Smart Program on sleep hygiene practices, sleep health efficacy, and behavioral well-being

Abstract: Objectives Using a social learning model, the aim of the Sleep Smart Program was to primarily improve sleep health behaviors and secondarily improve academic performance and behavioral well-being. Design Randomized control trial for a social learning-based preventive intervention program. Participants A diverse group of seventh graders from 2 urban, middle schools were randomly assigned, according to school, to an 8-session Sleep Smart Program (SS = 70) or a comparison group (comparison = 73). Measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 45 publications
1
52
0
3
Order By: Relevance
“…However, in 1 school-based intervention where school start time was delayed by 30 minutes, mean sleep duration increased by 45 minutes after the delay was instituted, and there was a decrease in the percentage of students who rated themselves as being unhappy, or depressed and irritated, or annoyed. 51 Likewise, Wolfson et al 52 recently reported a declining trend in internalizing symptoms among those in the seventh grade who participated in a school-based sleep hygiene educational intervention compared with a control school. In light of the high prevalence of suboptimal sleep patterns in adolescents, further studies are warranted to assess whether sleep pattern interventions may benefit adolescent mental health.…”
Section: Discussionmentioning
confidence: 99%
“…However, in 1 school-based intervention where school start time was delayed by 30 minutes, mean sleep duration increased by 45 minutes after the delay was instituted, and there was a decrease in the percentage of students who rated themselves as being unhappy, or depressed and irritated, or annoyed. 51 Likewise, Wolfson et al 52 recently reported a declining trend in internalizing symptoms among those in the seventh grade who participated in a school-based sleep hygiene educational intervention compared with a control school. In light of the high prevalence of suboptimal sleep patterns in adolescents, further studies are warranted to assess whether sleep pattern interventions may benefit adolescent mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating the effectiveness of psychoeducative interventions for improving sleep hygiene among adolescents [26][27][28][29][30][31][32][33] have yielded mixed results. While some studies report improvements in sleep duration [27,31] and sleep quality and wellbeing [31], others report only partial or no improvements in any outcomes [28,29,31,33]. It has been argued that parental involvement in sleep hygiene interventions for adolescents might be crucial in augmenting intervention effects [34].…”
Section: Psychoeducation To Improve Sleep Hygiene Amongst Adolescentsmentioning
confidence: 99%
“…Several sleep hygiene programs have been developed and their efficacy has been tested in randomized, controlled studies. Depending on the specific program, different positive outcomes have been achieved, such as longer sleep duration, earlier bed times, and reduced discrepancy between sleep timing on weekdays and on weekends (Kira, Maddison, Hull, Blunden, & Olds, 2014;Moseley & Gradisar, 2009;Wolfson, Harkins, Johnson, & Marco, 2015). However, the observed changes did not always concern all students, and often disappeared at the last follow-up assessments.…”
Section: Advancing Sleep Timing In Adolescents (Especially Late Chronmentioning
confidence: 99%